Uncommon Readers : Denis Donoghue, Frank Kermode, George Steiner, and the Tradition of the Common Reader. - Knight, Christopher J. (Studies in book and print culture., 2003)
Original and deliberative, Uncommon Readers presents a renewed defense of the tradition of the common reader.